The Use of Antioxidant Potential of Chokeberry Juice in Creating Pro-Healthy Dried Apples by Hybrid (Convection-Microwave-Vacuum) Method - Jolanta Kowalska; Agata Marzec; Ewa Domian; Sabina Galus; Agnieszka Ciurzyńska; Andrzej Lenart; Hanna Kowalska (Molecules, 2020)
The visible trend in the development of the snack market focuses on the use of innovative technologies such as low-temperature or hybrid processes that allow the preservation of native ingredients of raw plant materials. In addition, the high antioxidant potential of, for example, chokeberry fruit can be used to support technological processes and create new products. The aim of the study was to evaluate the possibility of using chokeberry juice concentrate as a component of an osmotic solution to enrich apple samples with natural bio-ingredients and obtain dried apples with increased content of ingredients with antioxidant properties; pro-healthy apple chips. The research material consisted of apples that underwent osmotic dehydration in solutions of sucrose or sucrose and chokeberry juice concentrate and then were dried by the freeze-drying or the hybrid method. The freeze-drying was more beneficial for maintaining the vitamin C content, while the use of the hybrid method resulted in the preservation of more polyphenolic compounds. The sensory evaluation indicated the need to modify the composition of the osmoactive solution. Due to the use of chokeberry juice concentrate, the content of vitamin C, polyphenols, and the antioxidant activity of dried apples was increased.